Effects of Early Sea-Ice Reduction on Zooplankton and Copepod Population Structure in the Northern Bering Sea During the Summers of 2017 and 2018 - Kimura, Fumihiko; Matsuno, Kohei; Abe, Yoshiyuki; Yamaguchi, Atsushi (Frontiers in Marine Science, 2022)
A remarkable early sea-ice reduction event was observed in the northern Bering Sea during 2018. In turn, this unusual hydrographic phenomenon affected several marine trophic levels, resulting in delayed phytoplankton blooms, phytoplankton community changes, and a northward shift of fish stocks. However, the response of the zooplankton community remains uncharacterized. Therefore, our study sought to investigate the zooplankton community shifts in the northern Bering Sea during the summers of 2017 and 2018 and evaluate the effects of early sea-ice melt events on the zooplankton community, population structure of large copepods, and copepod production. Five zooplankton communities were identified based on cluster analysis. Further, annual changes in the zooplankton community were identified in the Chirikov Basin. In 2017, the zooplankton community included abundant Pacific copepods transported by the Anadyr water. In 2018, however, the zooplankton community was dominated by small copepods and younger stages of large copepods (Calanus glacialis/marshallae and Metridia pacifica), which was likely caused by reproduction delays resulting from the early sea-ice reduction event. These environmental abnormalities increased copepod production; however, this higher zooplankton productivity did not efficiently reach the higher trophic levels. Taken together, our findings demonstrated that zooplankton community structure and production are highly sensitive to the environmental changes associated with early sea-ice reduction (e.g., warm temperatures and food availability).